2013
DOI: 10.4321/s1130-01082013000900003
|View full text |Cite
|
Sign up to set email alerts
|

Periodic gastroenterology and hepatology meetings with primary care: reasons for consultation

Abstract: Introduction: care overload, aging of population, and increased chronic diseases lead to increased referrals from primary care, which may sometimes overload the health system. Thus, different interventions have been carried out attempting to improve these aspects.Objectives: to assess the most frequent causes of consultation of general physicians, both in joint consultations and clinical sessions held jointly with specialist consultant in primary care, in the urban and rural setting, and the influence on refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…(6) Building capacity within primary care on common referral scenarios can help reduce the number of referrals to subspecialty services, thus increasing time for more urgent consultations and sicker patients. (7)…”
Section: Introductionmentioning
confidence: 99%
“…(6) Building capacity within primary care on common referral scenarios can help reduce the number of referrals to subspecialty services, thus increasing time for more urgent consultations and sicker patients. (7)…”
Section: Introductionmentioning
confidence: 99%
“…As part of patient- and disease-related factors, authors specified that highly prevalent health conditions were focused on in the interventions. Authors reported on the respective condition’s burden on healthcare facilities or system resources such as high consultation rates [ 30 31 35 ] or costs [ 36 37 38 39 40 41 ]. Furthermore, projects presented that the health condition of interest is a leading cause of morbidity, hospitalisations and death [ 37 38 39 40 42 43 44 45 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…two projects were from Australia [ 49 52 53 ], Brazil [ 47 51 ], Spain [ 35 54 ], Switzerland [ 33 34 45 ] and the Netherlands [ 27 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations